Analisis Deskriptif Tingkat Kesehatan Mental Mahasiswa dalam Menghadapi Tuntutan Akademik di Perguruan Tinggi - Dea Vara Amelia; Nadia Risqi Sabita; Pratiwi, Rani; Nalim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Mental health has become a critical issue in higher education, particularly in relation to the academic demands faced by students. This study aims to describe the level of mental health among students in coping with academic demands using a quantitative descriptive approach. The study subjects were 55 active students from various faculties at UIN K.H. Abdurrahman Wahid Pekalongan, selected using a combination of stratified random sampling and convenience sampling techniques. Data were collected using a structured questionnaire consisting of 20 items on a five-point Likert scale and analyzed using descriptive statistics. The results indicate that the majority of students (52.7%) fall into the “Fairly Healthy” category, with an overall average score of 62.00 (SD = 10.78). However, 21.8% of students fall into the “Unhealthy” to “Very Unhealthy” categories, indicating a concerning prevalence of mental health conditions. The most dominant academic stressor was pressure related to the Cumulative Grade Point Average (CGPA) target (mean = 2.98), followed by sleep disturbances (mean = 2.93) and lack of rest time due to a packed class schedule (mean = 2.91). Emotionally, students exhibited an ambivalent profile: relatively adequate social support (mean = 3.75), yet they experienced significant academic anxiety (mean = 2.40) and difficulty concentrating (mean = 2.35). These findings suggest that students’ mental health issues are not solely caused by the volume of coursework, but are more significantly influenced by systemic psychological pressures. Higher education institutions are recommended to develop proactive mental health services, review the curriculum workload, and reduce the stigma surrounding mental health on campus.